Conductive composites of serigraphic inks and their usage in heavy metal sensor and biosensor - Cankurtaran, Husnu; Karadayi, Emel Berber; Sungur, Sidika (ELSEVIER SCIENCE SA, 2016)
In this study, an epoxy based transparent serigraphic ink with its hardener was used for preparing the graphite composite electrodes. A mercury film coated epoxy based tubular graphite electrode was used for trace analysis of Pb2+ ion using square wave anodic stripping voltammetry (SWASV). The detection limit of lead was reasonable as 0.98 mu g/L for ten minutes reductive deposition time. The optimized method was applied to determine lead content in ground and waste water sample. A similar epoxy composite was also used to prepare the disposable planar thick film electrodes on silver-patterned epoxy circuit board substrates. The electrochemical performances of these planar electrodes against ferrocyanide ion, ascorbic acid and thioacetic acid were investigated by using cyclic voltammetry. Furthermore, the enzyme modified planar electrodes were used for the pesticide (aldicarb) determination. The results showed that the planar thick film and mercury coated tubular composite electrodes were suitable for sensitive analysis of common analytes and for further modifications. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Serigraphic ink; Conductive inks; Sensor; Heavy metal analysis; Biosensor; SCREEN-PRINTED ELECTRODE; VOLTAMMETRY; INKJET; Chemistry; Materials Science